INFORMATION TECHNOLOGY FOR PREDICTING THE RELIABILITY LEVEL OF TEXT MESSAGES (Computer systems and information technologies, 2025)
The research presents the results of the creation of an intellectualized information technology for predictive analysis of the reliability of text information messages, formed on the basis of concepts and tools of fuzzy logic. The use of the fuzzy set apparatus makes it possible to take into account the semantic ambiguity inherent in a natural language, as well as to formalize qualitative expert assessments by using linguistic variables, fuzzy term-sets and a rule base of the “if-then” type. This provides the possibility of creating adaptive decision-making models in conditions of incompleteness, inconsistency and subjectivity of input information.The developed technology includes fuzzification of input characteristics of texts, aggregation of expert judgments, construction of a system of fuzzy rules for assessing the reliability level and defuzzification of the obtained results. A concept is implemented that allows for a predictive assessment of the veracity of data even before their potential appearance in the information space. Within the framework of the proposed approach, a structured information database is formed, which establishes a relationship between the input variables, their linguistic nature, permissible ranges of values of the universal term-set, as well as clearly defined linguistic terms used for qualitative interpretation of parameters. Based on the performed structuring of linguistic variables of the studied process, a method of logical inference is developed, which represents a multi-level hierarchy of relationships between database components and determines the algorithm for calculating the message reliability indicator. The method is based on a knowledge matrix, leading to the construction of fuzzy logical equations, which provide the calculation of normalized values of membership functions of linguistic variables at the division points of the universal set. The result is the defuzzification of the fuzzy set “the indicator of the reliability level of text information messages” and the calculation of its value using the centre of mass formula, taking into account the input data. As a result of the study, a structural model of the information technology component of assessing the veracity of news content is developed.
Keywords: reliability of text messages; linguistic variable; logical inference method; knowledge matrix; membership function; fuzzy logic equations; information technology